Missiles for all the new global threat. - Oberg, J. (IEEE spectrum)
More and more Third World nations are acquiring ballistic missiles, some even of intercontinental range. A flourishing underground trade in technology and expertise, and the ease with which simpler missiles can be built, keeps the market going. These issues are discussed with reference to Scud missile and North Korean missile developments